(untitled) (Research, Society and Development, 2023)
Facial injuries, particularly soft tissue injuries and fractures of the facial bones, frequently occur as a result of motor vehicle collisions, falls, violent assaults, and collisions during recreational activities such as cycling. Although they occasionally occur as isolated injuries, they are more commonly associated with other serious injuries. Thus, the objective of this study was to describe the pre- and postoperative management of patients with cranio-maxillofacial trauma, as well as to describe behaviors that help professionals to establish the correct diagnosis, jointly determining their prognosis. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were contemplated between the years 2000 to 2022. The management of the injured face has undergone major changes after a greater understanding of the healing process and with advances in technology. The results are considerably better than 30 years ago as more comprehensive assessment and management is now possible. However, today there are still challenges to consistently restore trauma patients back to their pre-injury form and function, but this is not always possible. Greater understanding and development have significantly improved results, although controversy still exists in some areas.